The Developmental History of Ponorogo Batik Motif and Its Educational Values - Dhinar Ayu Maharani; Parji Parji; Sudarmiani Sudarmiani (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
The research discusses the development history of Ponorogo batik motif  in Ponorogo Regency 2007-2014 and its Educational Values. Ponorogo is one area which is growing in batik motif that has general motive called Reog Ponorogo motive. The development of batik in Ponorogo had decreased and 2007 was a year that was resurrection of batik Ponorogo pioneered by batik artisans. The method used in this research is the method of historical research. The results showed that batik Ponorogo begins with the temporary extinction of batik Ponorogo around 1960 which is caused by the emergence of printing of batik (print screen printing batik),batik Ponorogo has 17 patterns that are most influenced by history or the icon Ponorogo regency, and the development of batik Ponorogo motive that was experiencing growth from 2007 to 2009 that has seven classical motives then the development of contemphorery in 2009 and 2013 had five contemporary motives thenThe developments in 2014 that the government arranged a contest batik Ponorogo design batik produced five batik Ponorogo motive.